2019
DOI: 10.3390/antiox8050112
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonoid Quercetin Induces AP-1 Activation in FRTL-5 Thyroid Cells

Abstract: Previous studies have shown that quercetin inhibits thyroid function both in vitro and in vivo. An attempt to evaluate the effect of quercetin at the promoter level of the thyroid-specific genes led to the observation that this compound induces the basal activity of the reporter vector. Therefore, the action of quercetin has been evaluated on the basal activity of several reporter vectors: The PGL3 basic, promoter and control vectors from Promega, and a pSV-based chloramphenicol acetyltransferase (CAT) reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 42 publications
2
57
0
Order By: Relevance
“…Chitosan (CS) has emerged as a strong candidate scaffold for TE applications. Originating from chitin, chitosan is a unique natural polysaccharide with superb properties: high biodegradability, biocompatibility, non-antigenicity, adsorption capabilities, and antimicrobial activity (Giuliani, 2019). Studies have also found no complications, such as inflammation or allergic reactions, Tayeb et al (2018), Dutta et al (2019) following implantation of CS-based scaffolds (Keller et al, 2017).…”
Section: Chitosanmentioning
confidence: 99%
“…Chitosan (CS) has emerged as a strong candidate scaffold for TE applications. Originating from chitin, chitosan is a unique natural polysaccharide with superb properties: high biodegradability, biocompatibility, non-antigenicity, adsorption capabilities, and antimicrobial activity (Giuliani, 2019). Studies have also found no complications, such as inflammation or allergic reactions, Tayeb et al (2018), Dutta et al (2019) following implantation of CS-based scaffolds (Keller et al, 2017).…”
Section: Chitosanmentioning
confidence: 99%
“…Since Gal-3 recognizes and binds glycoprotein oligosaccharides through the carbohydrate recognition region, the pharmacological inhibitory effect of Gal-3 is mediated by CRD to inhibit the activity of the protein. Given the multiple effects of Gal-3 and its various localizations in tissues, such as intracellular, membrane-bound or extracellular, different inhibitors with different types of cellular uptake have been synthesized [ 98 , 99 ]. At present, these inhibitors are generally classified into carbohydrate and peptidic noncarbohydrate types.…”
Section: Main Textmentioning
confidence: 99%
“…A recent study showed that Rg1 could attenuate chronic, unpredictable, mild stress-induced, depressive-like effects in rats via the regulation of the nuclear factor (NF)-κB/NLRP3 pathway (21). It was also seen that Rg1 could protect primary astrocyte cultures against oxygen-glucose deprivation/reoxygenation (OGD/R)-induced injury, by decreasing ROS generation (22). A recent study also showed that Rg1 could alleviate age-associated neuronal damage by decreasing NOX2-mediated ROS generation and inhibiting NLRP1 inflammasome activation in neurons (23).…”
Section: Ginsenoside Rg1 Alleviates Lipopolysaccharide-induced Neuronal Damage By Inhibiting Nlrp1 Inflammasomes In Ht22 Cellsmentioning
confidence: 99%